2019
DOI: 10.3390/nu11112581
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Fructose Intake Impairs Baroreflex Sensitivity and Led to Elevated Blood Pressure in Rats

Abstract: Hypertension development with an increased intake of added sugar, especially excessive fructose intake, was shown in the National Health and Nutrition Examination Survey (NHANES) data. However, the mechanism underlying blood pressure (BP) elevation with increased fructose intake is still unclear. First, the present study showed that in rats fed 10% fructose for one week, BP and fructose/glucose levels increased in the central and peripheral nervous system. Furthermore, increased fructose intake resulted in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Previous studies have suggested that high levels of pure fructose intake contribute to elevation in blood pressure [ 6 , 18 , 19 , 20 , 21 , 22 ]. This observation has been confirmed in animal studies, where consuming a diet comprising 60% of total energy from fructose induces hypertension [ 23 , 24 , 25 , 26 , 27 ]. Few studies have examined the possible deleterious health effects of pure fructose consumption among adolescents [ 6 ], despite the observation that adolescents are the highest consumers of fructose [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 65%
“…Previous studies have suggested that high levels of pure fructose intake contribute to elevation in blood pressure [ 6 , 18 , 19 , 20 , 21 , 22 ]. This observation has been confirmed in animal studies, where consuming a diet comprising 60% of total energy from fructose induces hypertension [ 23 , 24 , 25 , 26 , 27 ]. Few studies have examined the possible deleterious health effects of pure fructose consumption among adolescents [ 6 ], despite the observation that adolescents are the highest consumers of fructose [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 65%
“…These factors, in combination with metabolic stress and energy alterations, may have decreased conduction speed and neural activity after HFI. 61 , 95 …”
Section: Discussionmentioning
confidence: 99%
“…35,107 Interestingly, HF intake decreased baroreflex sensitivity within a week (day 1) and induced a progressive reduction in baroreflex sensitivity over time. 104,106 But the alteration of oxidative stress-related markers was found at day 15 or later. 106 These results indicate that baroreflex sensitivity impairment occurs before increased oxidative stress.…”
Section: Impaired Baroreflex Sensitivity Contributes To Hf-induced Sshmentioning
confidence: 98%
“…103 Experimental evidence suggests that chronic excessive fructose intake decreased baroreflex sensitivity in rats. [104][105][106] Both fructose-sweetened water consumption and HF corn syrup-sweetened soft drink consumption acutely reduced spontaneous baroreflex sensitivity in healthy humans. 35,107 Interestingly, HF intake decreased baroreflex sensitivity within a week (day 1) and induced a progressive reduction in baroreflex sensitivity over time.…”
Section: Impaired Baroreflex Sensitivity Contributes To Hf-induced Sshmentioning
confidence: 99%